SNP profiling of Elaeis oleifera (H.B.K) cortes germplasm in Ucayali, Peru using genotyping-by-sequencing (GBS) - Camacho Villalobos, Alina Alexandra (2025)
Objectives Elaeis oleifera, commonly known as the American oil palm, plays a crucial role in the agricultural economies of Central and South America due to its unique oil characteristics and resistance to certain diseases. Despite its importance, limited available genetic information has hindered the effective utilization of this species in breeding programs aimed at improving oil yield and disease resistance. This study employed Genotyping-bySequencing (GBS) to profile polymorphisms within Elaeis oleifera populations, the unique germplasm bank for Peru, located in Ucayali, Peru, aiming to characterize the gene pool. Data description The GBS analysis successfully identified 22,703 informative single-nucleotide polymorphisms (SNPs) across the twelve-year-old plant genomes (n=42). Observed heterozygosity (Ho=0.3086) and expected heterozygosity index (He=0.3385) were quantified. The fixation index (Fst=0.0048) indicated low genetic differentiation within the germplasm. However, the presence of two genetic clusters (C_1 and C_2) distributed homogenously within the studied population has been detected; the origin of these clusters could be mainly associated with the initial management of the germplasm nucleus within Peru. The extensive SNP dataset provides a comprehensive genetic map that is invaluable for the conservation and enhancement of Elaeis oleifera in our region.